Psychological growth in aging Vietnam veterans: redefining shame and betrayal - McCormack, Lynne; Joseph, Stephen (SAGE, 2014)
This study offers alternative interpretations of war-related distress embedded within the social and political context of the Vietnam War. Subjective interpretations from aging Vietnam veterans were analyzed using interpretative phenomenological analysis. A central theme—Moral authenticity: Overcoming the betrayal and shame of war—overarched five subordinate themes. Four subordinate themes encapsulated layers of war-related betrayal associated with shame. Shame was likely to be described as either (a) internal/sense of personal failure, with no acts of rage; or (b) external/reckless or threatening acts of others, engendering rage. A fifth theme, reparation with self, reflected humility, gratitude, and empathy, currently undefined domains of the growth construct.